Gamified flipped learning in a French foreign language class: Efficiency and student perception - Anane, Chiraz (Frontiers in Education, 2022)
To enhance student engagement in a French foreign language course, two active learning methods were combined: Flipped learning and gamification. This study aimed to explore the efficiency of these teaching methods in a foreign language course with beginner learners and to assess student's perception of the experience. A total of 215 students were enrolled in this university elective course. All sections were taught by the same instructor during one semester. All students experienced both the flipped learning methodology and a traditional teaching approach. The results indicate that students' scores in the gamified quizzes were better when they prepared in advance for the sessions and had a flipped learning session. Moreover, in a questionnaire that was completed at the end of the term, students reported that they preferred the flipped learning sessions because such sessions helped them to better understand and memorize the textual material. Students also appreciated the use of gamification tools to help them learn with interest.